2008
DOI: 10.1021/om8003674
|View full text |Cite
|
Sign up to set email alerts
|

Facile and Efficient Olefination of Aryl Halides Catalyzed by a Palladium Complex Containing a Heteroarene-Functionalized N-Heterocyclic Carbene

Abstract: Ag 4 (L) 4 ](PF 6 ) 4 and [Pd(L) 2 ](PF 6 ) 2 (L ) 3-(2,4-dimethyl-1,8-naphthyrid-7-yl)-1-picolylimidazolylidene) have been prepared and fully characterized. The silver compound consists of a Ag 4 ring with short Ag-Ag contacts displaying a butterfly conformation. The palladium complex exhibits a helical structure with palladium located in a square-planar environment with two carbene ligands and two pyridines in a cis arrangement. The palladium complex has proven to be a highly efficient catalyst for Heck coup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 96 publications
(29 citation statements)
references
References 77 publications
1
27
0
1
Order By: Relevance
“…Heteroarene functionalized N-heterocyclic carbene ligands have proven to be good donating ligands for the assemblage of new metal clusters [63][64][65][66][67][68][69][70] 2 ](PF 6 ) 2 , (L1 = 1,3-bis(picolyl)benzimidazolylidene, L2 = 1-benzyl-3-picolylbenzimidazolylidene, L3 = 1,4-di(Nbenzylbenzimidazoliumyl)but-2-yne) containing bidentate or tridentate functionalized benzimidazolin-2-ylidene ligands. Seven silver and gold complexes were analyzed by X-ray single-crystal diffraction.…”
Section: Introductionmentioning
confidence: 99%
“…Heteroarene functionalized N-heterocyclic carbene ligands have proven to be good donating ligands for the assemblage of new metal clusters [63][64][65][66][67][68][69][70] 2 ](PF 6 ) 2 , (L1 = 1,3-bis(picolyl)benzimidazolylidene, L2 = 1-benzyl-3-picolylbenzimidazolylidene, L3 = 1,4-di(Nbenzylbenzimidazoliumyl)but-2-yne) containing bidentate or tridentate functionalized benzimidazolin-2-ylidene ligands. Seven silver and gold complexes were analyzed by X-ray single-crystal diffraction.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] Because of the high cost of palladium salts and the air-sensitivity and toxicity of phosphine-based ligands, alternative metals as well as ligands have been developed. [15][16][17][18][19][20][21][22][23][24][25] In the past few years, iron salts, as one of the most inexpensive and environmentally friendly salts on the earth, have been proved to be efficient catalysts for carbon-carbon and carbon-heteroatom bond formation. [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] Recently, Shao, Lu and co-workers found that 2,2p-diamino-6,6p-dimethylbiphenyl (L), as a non-phosphine compound, is a good ligand in the transition metal catalysed carbon-carbon bond formation reactions.…”
mentioning
confidence: 99%
“…Furthermore, the steric topography around the Pd is crucial, with bulkier NHC Nsubstituents generally leading to higher catalytic activity. 28 Pd complexes in which a pyridyl donor is tethered to the NHC ligand have previously been reported [30][31][32][33][34] and, in some cases, the steric effects of the ligand have been examined in catalysis. 35 Following our recent findings regarding the electronic effects of hemilabile NHC-appended pyridyl donors on Cu, 36 it was decided to prepare a family of related complexes with Pd.…”
Section: 29mentioning
confidence: 99%